(untitled) (Journal of Environmental Bioremediation and Toxicology, 2014)
Newer discovery of Salmonella strains warranted the development of newer ELISA system. The aim of this works is to develop a sensitive and simple indirect ELISA for the detection of Salmonella Typhimurium using formalin- and heat-killed cells as immunogens. The parameters of the resultant calibration curve for the formalin-killed cells (FKC) were minimum absorbance of 0.101± 0.011, maximum absorbance of 2.804± 0.020, slope parameter of 1.197, while c, the concentration that results in 50% response was 4.22 x 106 CFU/ml. The LOD and LOQ were 19,300 and 52,700 CFU/mL, respectively. The parameters of the typical calibration curve for heat-killed cells (HKC) were minimum absorbance of 0.115± 0.013, maximum absorbance of 2.810± 0.021, slope parameter was 1.441, while c, the concentration that results in 50% response was 2.15 x 106 CFU/ml. The LOD and LOQ were 47,100 and 123,000 CFU/mL, respectively. Antibody raised to FKC was twice the sensitivity and approximately ten times the linear range compared to antibody raised to HKC. Antibody produced from formalin-killed cells exhibited lower cross reactivity than heat-killed cells. The results of this work could open new avenues on optimization of antigen preparation for maximal sensitivity of the developed polyclonal antibody.